The social media revolution is changing the conference experience: analytics and trends from eight international meetings. (26th January 2015) - Wilkinson, Sarah E.; Basto, Marnique Y.; Perovic, Greta; Lawrentschuk, Nathan; Murphy, Declan G.
<x xml:space="preserve">Abstract</x> Objective To analyse the use of Twitter at urology conferences to enhance the social media conference experience. Materials and Methods We prospectively registered the hashtags of eight international urology conferences taking place in 2013, using the social media metrics website, Symplur.com. In addition, we prospectively registered the hashtag for the European Association of Urology (EAU) Annual Congress for 3 consecutive years (2012–2014) to analyse the trend in the use of Twitter at a particular meeting. Metrics including number of 'tweets', number of participants, tweet traffic per day, and overall digital impressions, which were captured for 5 days before each conference, the conference itself, and the following 2 days. We also measured corresponding social media activity at a very large non‐urology meeting (the American Society of Clinical Oncology) for comparative purposes. Results Twitter activity was noted at all eight conferences in 2013. In all, 12 363 tweets were sent generating over 14 million impressions. The number of participants tweeting at each meeting varied from 80 (Congress of the Société Internationale d'Urologie, #SIU2013) to 573 (the American Urological Association, #AUA13). Overall, the AUA meeting (#AUA13) generated the most Twitter activity with >8.6 million impressions and a total of 4663 tweets over the peri‐conference period. It also had the most impressions and tweets per day over this period, at 717 000 and 389, respectively. The EAU Annual Congress 2013 (#EAU13) generated 1.74 million impressions from a total of 1762 tweets from 236 participants. For trends in Twitter use, there was a very sharp rise in Twitter activity at the EAU Annual Congress between 2012 and 2014. Over this 3‐year period, the number of participants increased almost 10‐fold, leading to an increase in the number of tweets from 347 to almost 6000. At #EAU14, digital impressions reached 7.35 million with 5903 tweets sent by 797 participants. Conclusions Urological conferences, to a varying extent, have adopted social media as a means of amplifying the conference experience to a wider audience, generating international engagement and global reach. Twitter is a very powerful tool that amplifies the content of scientific meetings, and conference organisers should put in place strategies to capitalise on this.